ENDEMIA OCULTA DE HANSENÍASE EM MUNICÍPIOS DO ARQUIPÉLAGO DO MARAJÓ, PA - SOUZA, Louise Sousa de; MESSIAS, Ana Caroline; BOUTH, Raquel; JORGE, Erika; SILVA, Sâmela; PINTO, Pablo; SANTOS, Andrea; BARRETO, Josafá; SILVA, Moises; SALGADO, Claudio (Hansenologia Internationalis: hanseníase e outras doenças infecciosas, 2019)
.